Foot care practices among patients with diabetes mellitus in South-Western Nigeria - Taoreed Adegoke Azeez; Martins Ehizode Emuze (APIK Journal of Internal Medicine, 2022)
Introduction: Diabetes foot care is an evidence-based means of preventing diabetes foot ulcer. The components of diabetic foot care include yearly comprehensive foot examination, prompt identification of risk factors to diabetic foot ulcer, diabetes foot education, and standard footwear practices. This study is aimed at evaluating the foot care practices of patients with diabetes in a tertiary hospital in South-Western Nigeria. Methods: It is a cross-sectional study that employed standardized pretested structured questionnaire to obtain data from 100 participants. The study was conducted at the diabetes clinic of a tertiary hospital in South-Western Nigeria. Ethical approval was obtained from the Institutional Review Board of the hospital. Data were presented in tables and charts. Descriptive and analytical statistics was done with Statistical Package for the Social Sciences (SPSS) version 22. Results: The mean age of the participants was 58.8 ± 11.8 years. There were 66 females and 34 males. The study showed that 77% of the participants were not having yearly comprehensive examination although 94% of the respondents did daily foot inspection at home. Only 16% had continuous foot education. Moreover, only 11% of the respondents wear recommended shoes, but 88% inspected their shoes before wearing them. Sadly, 11% of the respondents walked barefooted at home. The health-seeking behavior of respondents in an event of foot ulceration was significantly associated with their educational status. Conclusion: Foot care practices of the respondents were sub-standard. So, there is an urgent need to reinforce foot care education so as to improve these subpar practices.